1979
DOI: 10.2307/2042705
|View full text |Cite
|
Sign up to set email alerts
|

A Right PCI Ring is Right Noetherian

Abstract: Abstract. C. Faith and J. Cozzens have shown that a ring, whose right proper cyclic modules are injective, is either semisimple or a simple, right semihereditary, right Ore K-domain. They have posed a question as to whether such a ring is right noetherian. In this paper, an affirmative answer is given to that question. Moreover, necessary and sufficient conditions are given as to when a right PCI ring is left PCI.In [1], Faith and Cozzens proved that a ring R whose proper right cyclic modules are injective mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 3 publications
0
9
0
1
Order By: Relevance
“…Faith called a ring R a right PCI ring if every cyclic right R-module is injective or isomorphic to R R . By his result in [11] and a result of Damiano in [6] such a ring is either semisimple or it is a non-artinian, right hereditary, right noetherian, simple domain. The latter ring is usually called a right PCI domain.…”
Section: Some Remarksmentioning
confidence: 99%
“…Faith called a ring R a right PCI ring if every cyclic right R-module is injective or isomorphic to R R . By his result in [11] and a result of Damiano in [6] such a ring is either semisimple or it is a non-artinian, right hereditary, right noetherian, simple domain. The latter ring is usually called a right PCI domain.…”
Section: Some Remarksmentioning
confidence: 99%
“…Faith [6] studied the structure of right PCI-rings, i.e., rings whose proper right cyclic modules are injective, and he left open the question of whether right PCI-rings must be right Noetherian. In [3] Damiano gave an affirmative answer to Faith's question. The key result in [3] was the fact that a proper cyclic finitely presented module Mr over a right PCI-domain 7?…”
mentioning
confidence: 99%
“…In [3] Damiano gave an affirmative answer to Faith's question. The key result in [3] was the fact that a proper cyclic finitely presented module Mr over a right PCI-domain 7? has a semisimple endomorphism ring S [3, Proposition].…”
mentioning
confidence: 99%
“…More recently, in Huynh-Dung [4], an attempt was made to generalize Osofsky's theorem to cyclic injective modules. Using a result of Damiano [3], it was shown in [4] that a cyclic finitely presented module is semisimple if all quotients of cyclic submodules of M are injective. In the recent work [8], Osofsky and Smith have shown that the hypothesis "finitely presented" can be removed.…”
mentioning
confidence: 99%